Evaluasi Pendidikan Perspfektif Al-Quran (Al-Mas’ul/المسؤل, Al-Ahsha/ الاحصاء , Al-‘Adad/ العدد, Al-Bala/ البلاء, Al-Fitnah/ الفتنة) - Taubatan Nasuha; Muhibuddin Zaini (Jurnal Pendidikan Agama Islam, 2025)
Evaluation is a component of the education system that must be carried out systematically and in a planned manner as a tool to measure success or targets to be achieved in the educational process. Success and failure in learning can be identified through evaluation. Likewise, all human activities, whether individual or group, must be evaluated with the aim of improving performance and achieving better results. The concepts of evaluation in the Quran include Al-Mas'ul, Al-Ahsha, Al-Adad, Al-Bala', Al-Fitnah. This paper aims to understand the concept of educational evaluation from the perspective of the Quran. The results of this study evaluate education contained in the Al-Quran Al-Mas'ul (responsibility, Al-Isra verse 36 and Al-Ahzab verse 15), Al-Ahsha' (Surat Maryam verse 94 and Yasin verse 12), Al-Adad (Surat Yunus verse 5 and Maryam verse 84), Al-Bala' (Surat Al-Anbiya verse 35 and Ali Imran verse 186), Al-Fitnah (Surat Al-Anfal verse 28 and At Thagabun verse 15)